A Silylene–Germylene Molecule Containing a SiI−GeI Single Bond. Issue 28 (8th May 2020) - Qin, Yingying; Zheng, Gang; Guo, Yan; Gao, Fangfang; Ma, Jiani; Sun, Wei; Xie, Gang; Chen, Sanping; Wang, Yaoyu; Sun, Huaming; Li, Anyang; Wang, Wenyuan
Abstract: The first isolable silylene–germylene complex 5 was assembled by a salt metathesis reaction between the germylene anion 3 and the N‐heterocyclic chlorosilylene 4, and structurally characterized. The central structure of 5 demonstrates a remarkable gauche ‐bent geometry with the silylene and germylene units, which are interconnected by a Si−Ge bond with a length of 2.4498(9) Å. This value is not only perceptibly longer than the distances known in doubly bonded germasilenes, and also slightly longer than those in germylsilanes. The DFT calculations on 5 confirmed a nearly nonpolar Si I −Ge I single‐bond nature and its bonding orbital, as well as the aromaticity of the C3 NGe‐rings in 3 and 5 . The latter increases the molecular stability of 3 and 5, and makes the preparation of silylene–germylene complex 5 a reality. Abstract : Being the first : The first interconnected silylene–germylene complex was synthesized and structurally characterized. Its central molecular structure demonstrates a striking gauche ‐bent geometry with a Si I −Ge I distance of 2.4498(9) Å. DFT calculations confirmed a nearly nonpolar Si−Ge single bond nature and its bonding orbital. This molecule offers the unique silicon‐containing heteroleptic alkyne analogue of heavier Group 14 elements.